1986
DOI: 10.3109/07420528609066353
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Rhythms in Neurotransmitter Receptors in Discrete Rat Brain Regions

Abstract: Circadian rhythms were measured in alpha 1-, alpha 2- and beta-adrenergic, acetylcholine muscarinic (ACh), and benzodiazepine (BDZ) receptor binding in small regions of rat brain. Rhythms in alpha 1-receptor binding were measured in olfactory bulb, frontal, cingulate, piriform, parietal, temporal and occipital cortex, hypothalamus, hippocampus, pons-medulla, caudate-putamen and thalamus-septum. No rhythm was found in cerebellum. Rhythms in alpha 2-receptor binding were measured in frontal, parietal and tempora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Indeed some of the major neurotransmitters that have been implicated in mood regulation, including serotonin, norepinephrine and dopamine, have a circadian rhythm in their levels, release, and synthesis-related enzymes (Weiner et al, 1992;Shieh et al, 1997;Aston-Jones et al, 2001;Barassin et al, 2002;Khaldy et al, 2002;Castaneda et al, 2004;Weber et al, 2004;Malek et al, 2005). There are also circadian rhythms in the expression and activity of several of the receptors that bind these neurotransmitters, suggesting that these entire circuits are under circadian control (Kafka et al, 1983;Wesemann and Weiner, 1990;Witte and Lemmer, 1991;Coon et al, 1997;Akhisaroglu et al, 2005). It seems likely that disruptions in the normal rhythms in these circuits (either continuous or abrupt) could have major effects on mood and motivational states.…”
Section: Influence Of the Molecular Clock On Mood-related Neurotransmmentioning
confidence: 99%
“…Indeed some of the major neurotransmitters that have been implicated in mood regulation, including serotonin, norepinephrine and dopamine, have a circadian rhythm in their levels, release, and synthesis-related enzymes (Weiner et al, 1992;Shieh et al, 1997;Aston-Jones et al, 2001;Barassin et al, 2002;Khaldy et al, 2002;Castaneda et al, 2004;Weber et al, 2004;Malek et al, 2005). There are also circadian rhythms in the expression and activity of several of the receptors that bind these neurotransmitters, suggesting that these entire circuits are under circadian control (Kafka et al, 1983;Wesemann and Weiner, 1990;Witte and Lemmer, 1991;Coon et al, 1997;Akhisaroglu et al, 2005). It seems likely that disruptions in the normal rhythms in these circuits (either continuous or abrupt) could have major effects on mood and motivational states.…”
Section: Influence Of the Molecular Clock On Mood-related Neurotransmmentioning
confidence: 99%
“…While spontaneous activity has often been associated with the mesolimbic dopaminergic system, an examination of circadian changes has indicated that dark-phase increases in several indices of CS function including dopamine receptors (36), content (37), turnover (38) and in vitro release (39) are associated with dark-phase increases in behavioral activity (38,40). Moreover, a significant correlation between striatal dopamine and spontaneous motor activity in both male and female rats has been reported (41) and there is also a strong positive correlption between in vivo striatal dopamine output as Dopamine release/locomotor behavior-intact vs castrate rats determined by detection of the dopamine metabolite, homovanillac acid (42,43), and dopamine biosynthesis (44) with circadian changes in spontaneous behavioral activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, hippocampal ACh and NE levels can vary in vivo, so that combined activation of G␣q-coupled signaling may be important physiologically to allow induction of plasticity even when ACh and/or NE are present at low levels. For example, ACh and NE levels fluctuate across the sleep-wake cycle, as hippocampal function alternates between memory encoding during wakefulness and consolidation during sleep (Hobson et al, 1975;Kafka et al, 1986;Aston-Jones et al, 1991;Hasselmo, 1999). Cholinergic and/or noradrenergic signaling can also be reduced in hippocampus during aging and neurodegenerative diseases (Carlsson et al, 1980;Tomlinson et al, 1981;Collerton, 1986;Springer et al, 1987;Bickford-Wimer et al, 1988;ChanPalay and Asan, 1989;German et al, 1992;Kasa et al, 1997).…”
Section: Introductionmentioning
confidence: 99%